Effect of dual targeting procyanidins nanoparticles on metabolomics of lipopolysaccharide-stimulated inflammatory macrophages - Shanshan Tie; Lijuan Zhang; Bin Li; Shanghua Xing; Haitao Wang; Yannan Chen; Weina Cui; Shaobin Gu; Mingqian Tan (Food Science and Human Wellness)
Inflammation plays an important role in the occurrence and development of many inflammatory diseases. The purpose of this study was to evaluate the anti-inflammatory effect and metabolic behavior of the dual targeting procyanidins (PC) nanoparticles on lipopolysaccharide (LPS)-stimulated inflammatory macrophages by metabolomics method. The double-targeting PC nanoparticles could specifically target both the CD44 receptor and mitochondria, while the single targeting PC-loaded nanoparticles that could target the CD44 receptor on the surface of macrophages. The double-targeting PC nanoparticles had better inhibitory effect than single-targeting PC nanoparticles on the leakage of lactate dehydrogenase and reactive oxygen species overexpression induced by LPS. Amino acid metabolism, energy metabolism and purine metabolism were disordered in LPS-treated group, and metabolic pathway analysis indicated that the double-targeting PC nanoparticles reversed some of LPS impacts. The changes of these potential biomarkers and their corresponding pathways are helpful to further understand the mechanism of PC nanoparticles in alleviating inflammation, and promote their application in nutrition intervention.